2003
DOI: 10.1590/s0100-40422003000500017
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização e estabilidade físico-química de sistemas poliméricos nanoparticulados para administração de fármacos

Abstract: Recebido em 28/10/02; aceito em 27/2/03 PHYSICOCHEMICAL CHARACTERIZATION AND STABILITY OF THE POLYMERIC NANOPARTICLE SYSTEMS FOR DRUG ADMINISTRATION. Polymeric nanoparticle systems such as nanocapsules and nanospheres present potential applications for the administration of therapeutic molecules. The physico-chemical characteristics of nanoparticle suspensions are important pre-requisites of the success of any dosage form development. The purpose of this review is to present the state of the art regarding the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
214
0
178

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 403 publications
(407 citation statements)
references
References 85 publications
(249 reference statements)
15
214
0
178
Order By: Relevance
“…15 The release of a drug from polymeric microparticles occurs through different mechanisms: desorption of the drug from the surface of the particles; diffusion of the drug through the pores of the polymeric matrix; erosion of the polymeric matrix; polymer degradation or a combination of different processes. 5,19 As PHB is very slowly degraded, the release profile of a drug from a PHB matrix is generally dependent on drug diffusion rather than on polymer degradation. 20 The results for the PHB molecular weight, pore size distributions and the morphology of the microparticles after the release assay indicated that the release of PXC from PHB microparticles occurs mainly through the two mechanisms: desorption of the drug from the surface of the particles and diffusion of the drug through the pores of the polymeric matrix.…”
Section: Discussionmentioning
confidence: 99%
“…15 The release of a drug from polymeric microparticles occurs through different mechanisms: desorption of the drug from the surface of the particles; diffusion of the drug through the pores of the polymeric matrix; erosion of the polymeric matrix; polymer degradation or a combination of different processes. 5,19 As PHB is very slowly degraded, the release profile of a drug from a PHB matrix is generally dependent on drug diffusion rather than on polymer degradation. 20 The results for the PHB molecular weight, pore size distributions and the morphology of the microparticles after the release assay indicated that the release of PXC from PHB microparticles occurs mainly through the two mechanisms: desorption of the drug from the surface of the particles and diffusion of the drug through the pores of the polymeric matrix.…”
Section: Discussionmentioning
confidence: 99%
“…This electric potential is influenced by changes in the particle interface with the dispersing medium, due to the dissociation of functional surface groups or the adsorption of ionic species present in the aqueous dispersion (Schaffazick, Guterres, 2003). The cellulose derivatives polymers, HPMC and EC, are non ionic materials and the CS is a positive polysaccharide due to the amino groups, which acquire electrical charge.…”
Section: Physicochemical Characterization Of Floating Microparticlesmentioning
confidence: 99%
“…7 Os fármacos podem ser encapsulados por diferentes mecanismos, que incluem solubilização ou retenção na nanopartícula, conjugação ou adsorção. 8 Em uma situação ideal as nanopartículas, atuando como nanocarreadores, são capazes de transportar o fármaco para um local de destino específico (receptor, sítio ativo) para exercer a sua atividade terapêutica com o máximo de segurança. Os principais nanocarreadores engenheirados aplicados na terapêutica são: os lipossomas, as nanopartículas lipídicas, as micelas e as nanopartículas poliméricas.…”
Section: Tipos De Nanocarreadores Biodegradáveisunclassified